INTERCULTURAL COMMUNICATION AND THE EXISTENCE OF JAMAICAN CULTURE “NAMOY BUDAYA” IN THE DIGITAL SPHERE - M. Ibnu Naufal Maskuri; Fitri Yanti; Ade Nur Istiani; Nadya Amalia Nasution; Hamdan Daulay (QAULAN: Journal of Islamic Communication, 2026)
Abstract: This study aims to analyze the form of intercultural communication that occurs through the digital work "Namoy Budaya" in its representation of Jamaican culture in the digital space. As a musician and DJ who blends elements of electronic music with Jamaican cultural values such as freedom, peace, and solidarity, 'Namoy Budaya" is a true example of cross-cultural communication practices in the era of digital globalization. The approach of this research is qualitative descriptive with in-depth interview techniques on "Namoy Budaya" as cultural communicators and some of their active followers as message recipients. Analysis was also carried out on digital content on social media to understand communication strategies and forms of cultural adaptation displayed. The results of the study indicate that “Namoy Budaya” employs three main intercultural communication strategies in the digital environment: the use of reggae music as a medium of cultural adaptation, visual symbols inspired by Jamaican identity combined with local Indonesian elements, and interactive digital narratives through social media engagement. The study also found that followers interpret “Namoy Budaya” as a representation of cultural hybridity, freedom of expression, and an alternative medium for global cultural education. These findings demonstrate how digital media facilitates the negotiation of global and local cultural identities in contemporary intercultural communication. This research confirms that intercultural communication in the digital space is not just an exchange of symbols, but also a creative process of building understanding and harmony between global and local cultures.